Identification of Key Gene Networks and Deciphering Transcriptional Regulators Associated With Peanut Embryo Abortion Mediated by Calcium Deficiency - Chen, Hua; Yang, Qiang; Fu, Huiwen; Chen, Kun; Zhao, Shanshan; Zhang, Chong; Cai, Tiecheng; Wang, Lihui; Lu, Wenzhi; Dang, Hao; Gao, Meijia; Li, Huaqi; et al. (Frontiers in Plant Science, 2022)
Peanut embryo development is easily affected by a variety of nutrient elements in the soil, especially the calcium level. Peanut produces abortive embryos in calcium-deficient soil, but underlying mechanism remains unclear. Thus, identifying key transcriptional regulators and their associated regulatory networks promises to contribute to a better understanding of this process. In this study, cellular biology and gene expression analyses were performed to investigate peanut embryo development with the aim to discern the global architecture of gene regulatory networks underlying peanut embryo abortion under calcium deficiency conditions. The endomembrane systems tended to disintegrate, impairing cell growth and starch, protein and lipid body accumulation, resulting in aborted seeds. RNA-seq analysis showed that the gene expression profile in peanut embryos was significantly changed under calcium deficiency. Further analysis indicated that multiple signal pathways were involved in the peanut embryo abortion. Differential expressed genes (DEGs) related to cytoplasmic free Ca2+ were significantly altered. DEGs in plant hormone signaling pathways tended to be associated with increased IAA and ethylene but with decreased ABA, gibberellin, cytokinin, and brassinosteroid levels. Certain vital genes, including apoptosis-inducing factor, WRKYs and ethylene-responsive transcription factors, were up-regulated, while key regulators of embryo development, such as TCP4, WRI1, FUS3, ABI3, and GLK1 were down-regulated. Weighted gene co-expression network analysis (WGCNA) identified 16 significant modules associated with the plant hormone signaling, MAPK signaling, ubiquitin mediated proteolysis, reserve substance biosynthesis and metabolism pathways to decipher regulatory network. The most significant module was darkolivegreen2 and FUS3 (AH06G23930) had the highest connectivity among this module. Importantly, key transcription factors involved in embryogenesis or ovule development includingTCP4, GLK1, ABI3, bHLH115, MYC2, etc. were also present in this module and down regulated under calcium deficiency. This study presents the first global view of the gene regulatory network involved in peanut embryo abortion under calcium deficiency conditions and lays foundation for improving peanut tolerances to calcium deficiency by a targeted manipulation of molecular breeding.